Pengaruh investasi, tenaga kerja dan unit usaha terhadap PDRB industri pengolahan di Provinsi Jambi - Rica Citra Meisi; Zulfanetti Zulfanetti; M. Syurya Hidayat (e-Journal Perdagangan Industri dan Moneter, 2021)
The research objectives are (1) to know the development and contribution of the manufacturing industry GDP (2) to know the development of investment, labor, and processing industry business units; and (3) knowing the effect of investment, labor and business units on processing industry GDP. The data used in this study are secondary data from the Jambi provincial Central Bureau of Statistics (BPS). To answer these goals, this study uses a type of quantitative descriptive research with an analysis model for the first and second problem using the contribution and development model, while the model for the third problem is multiple linear regression. The results of the study show that (1) the average development of the processing industry GDP in Jambi Province in 2000-2016 was 4.86 percent and its contribution was 12.07 percent; (2) the average investment development is 3.42 percent, the average workforce is 4.74 percent, the average business unit is 2.29 percent; and (3) simultaneously and partially investment, labor and business units significantly influence the GDP of the processing industry in Jambi province. Keywords: GDP, Investment, Employment, Business units.